Intertextual Criticism: Unveiling Literary Connections in Elif Shafak's Works (Raparin Journal of Humanities (RJH), 2023)
This paper explores the concept of intertextual criticism and its application in the works of renowned Turkish-British author Elif Shafak. By examining the intricate web of literary connections in Shafak's writings, this study aims at uncovering the intertextual tapestry woven within her narratives. The methodology involves close reading and analysis of selected works and a comprehensive survey of intertextual sources. The critical approach utilised is a comparative study, which examines the influences, allusions, and references to other literary works in Shafak's novels. The discussion highlights intertextuality's thematic, structural, and cultural implications in Shafak's works. Ultimately, this article concludes by emphasising the significance of intertextual criticism in enhancing our understanding of Shafak's unique literary contributions.